2001
DOI: 10.1046/j.1464-410x.2001.02356.x
|View full text |Cite
|
Sign up to set email alerts
|

The development and validation of a patient‐information booklet on ureteric stents

Abstract: Objective To report a scienti®c approach incorporating patient preferences towards the development of a patient-information booklet about ureteric stents. Patients and methods Phase 1 of the study included 35 adult patients with ureteric stents who were surveyed using semi-structured interviews (four patients) and a questionnaire (31 patients) to assess various issues relating to information given to patients about ureteric stents. In addition, published papers were assessed and clinicians' opinions sought. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 13 publications
0
17
0
2
Order By: Relevance
“…Alternatively, we could consider providing more information for patients regarding their treatment 9 and they could share the responsibility with their clinicians regarding tracking of their stents. We found that 5 patients organised their own further treatment and stent removal with their local hospitals and no stents were forgotten.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, we could consider providing more information for patients regarding their treatment 9 and they could share the responsibility with their clinicians regarding tracking of their stents. We found that 5 patients organised their own further treatment and stent removal with their local hospitals and no stents were forgotten.…”
Section: Discussionmentioning
confidence: 99%
“…1,6,7 Written education materials are therefore extremely important to supplement, reinforce and clarify messages which are poorly understood during consultation, facilitate patients' learning and aid recall. [7][8][9][10][11][12] They also provide the patients with consistent messages and allow flexibility of timing and delivery of information. Patients can refer to the written information whenever necessary and use them to learn at their own pace.…”
Section: Introductionmentioning
confidence: 99%
“…Questions were related to the PIL content. Patient involvement was necessary in order to assess understanding, acceptability, and content adequacy, and to clarify any ambiguities in the PIL and questionnaire [9,13,14]. For this purpose, a study was conducted to determine if the information provided was well communicated and satisfied people's needs.…”
Section: Methodsmentioning
confidence: 99%